Fetal heterozygosity for both Hb G-Hsi-Tsou and beta thalassemia: A case report - Elena Alhazidou; Maria Androulaki; Michail Panagiotopoulos; Dimitrios Boudouvas; Dionysia Lampropoulou; Eleni Yfanti; Evangelia-Eleni Delaki; Konstantina Repa; Georgios Petrakos (Elsevier, 2020)
Introduction: This case report describes a fetus with compound heterozygosity for Hb G-Hsi-Tsou and beta thalassemia, diagnosed in a healthy pregnancy. To the best of our knowledge, this is the first documented case of compound heterozygosity and the woman is the second known case of heterozygosity for Hb G-Hsi-Tsou. Case presentation: A 34-year-old woman during her first pregnancy underwent hemoglobin electrophoresis which revealed heterozygosity for Hb G-Hsi-Tsou. Hemoglobin G-Hsi-Tsou constitutes a hemoglobin variant with a structural abnormality of the beta chain, first described in 1972, but since then no other cases have been reported. After finding out that her husband was heterozygous for beta thalassemia, chorionic villus sampling revealed the embryo's heterozygosity for both Hb G-Hsi-Tsou and beta thalassemia. Due to lack of scientific data, the couple decided to end the pregnancy. Conclusion: It was not possible to determine whether the fetus would present serious deficiencies in hematopoiesis, as Hb G-Hsi-Tsou is a variant which is not yet fully understood. What made this case even more complex was the simultaneous presence of the beta thalassemia allele.